Association of humoral immunity status and thrombodynamics after vaccination with Gam-COVID-Vac and CoviVac - O. M. Drapkina; S. A. Berns; A. Yu. Gorshkov; L. N. Ryzhakova; A. A. Ivanova; A. V. Emelyanov; S. N. Voinova; R. A. Karateev; N. A. Arablinskiy; A. A. Rodionova; V. S. Bashnyak; M. S. Pokrovskaya (Кардиоваскулярная терапия и профилактика, 2022)
The ongoing pandemic of coronavirus disease 2019 makes it important to study the immunogenicity, the duration of immune response, and the safety of existing vaccines.Aim. As part of a prospective observational study, to assess associations between levels of anti-Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) S protein IgG antibodies and thrombodynamics parameters in individuals vaccinated with Gam-COVID-Vac and CoviVac vaccines.Material and methods. The study included 137 people who completed the first 3 visits: 30 people received the Gam-COVID-Vac, 107 people — CoviVac. The study participants underwent venous blood sampling before the introduction of the 1st and 2nd vaccine doses, as well as 42 days after the administration of 1st dose in order to quantify the level of IgG antibodies. At each visit, plasma hemostasis parameters were analyzed using a thrombodynamics test.Results. During the follow-up period, there was a clear increase in the level of anti-SARS-CoV-2 S protein IgG antibodies in both groups. At the same time, this increase over time was significantly greater in Gam-COVID-Vac group. There was no correlation detected between thrombodynamics test results and the levels of anti-SARS-CoV-2 S protein IgG antibodies.Conclusion. The data obtained demonstrate the ability of both vaccines to stimulate the production of anti-SARS-CoV-2 antibodies. However, immune response to Gam-COVID-Vac is much higher. The lack of correlation between thrombodynamics and the level of specific antibodies suggests that vaccination for COVID-19 with Gam-COVIDVac and CoviVac does not cause changes in plasma hemostasis and does not increase the risk of thrombosis.